"It felt like unfinished business, it feels like that's finished now": Women's experiences of decision making around contralateral prophylactic mastectomy (CPM). Issue 6 (24th April 2019) - Tollow, Philippa; Williams, Victoria Suzanne; Harcourt, Diana; Paraskeva, Nicole
Abstract: Objective: Increasing numbers of women in the United Kingdom are choosing to have a contralateral prophylactic mastectomy (CPM) after diagnosis of breast cancer. Whilst research suggests that many experience high rates of psychological well‐being after CPM, professional guidelines suggest CPM is "not required" for the majority of unilateral breast cancer patients, and some individuals consider the surgery to be controversial. Existing research has explored patients' reasons for seeking CPM; however, little is known about their experiences of decision making. This study aimed to investigate women's experiences of decision making around CPM in the United Kingdom. Methods: Semistructured qualitative interviews were conducted with 27 women, recruited through breast cancer support charities. All participants had CPM in the United Kingdom after a diagnosis of unilateral breast cancer, ductal carcinoma in situ (DCIS), or invasive ductal carcinoma. Data were analysed using thematic analysis. Results: Two main themes were generated from the analytic process: "sanity check" ("battling for CPM, " "feeling stigmatised, " "seeking similar others") and "reclaiming the body" ("being true to self, " "moving forward"). Women described defending their decision to have CPM, concerns that their thoughts about surgery may be considered "abnormal, " and seeking support from peers. The decision to have CPM was discussed in terms of their future relationship with their body and moving forward after cancer. Conclusions: This study highlights the importance of interactions with health care professionals in the decision‐making experience, the role of peer support, and the need to fully understand the potentially complex and multifaceted nature of each woman's decision to seek CPM.